Implementasi Logarithmic Image Processing Pada Color Constancy Citra Mozaik - Muhammad Fauzi Indra (Journal of Informatics, Electrical and Electronics Engineering, 2021)
Image as a multimedia component that plays a very important role as a form of visual information. The image has characteristics that are not owned by text data, namely the image is rich with information. In digital image capture, we often encounter color problems. Colors always change depending on the lighting conditions at that time. Color constancy is one of the features of the human vision system which strives for the color received from an object to look the same even though it is in different lighting conditions. The colors they have are black, gray, and white. The gray level here is the color of gray with various levels from black to close to white. Grayscale images are stored in an 8-bit format for each sample pixel, which allows as many as 256 intensities (256 gray color combinations). Logarithmic Image Processing (LIP) is a new mathematical approach that provides an outline framework for representation and processing, including logarithmic graylevel images in a limited range. Where consistent with non-linear logarithmics in the human visual system, the modified image is processed using the log function, which is to enable the conspicuous pixel boundaries of the grayscale to be able to see the effect of the range function.